The Role of Nursing and Epidemiology Professionals in Infectious Disease Control and Epidemic Prevention in Public Health Settings - Mamdoh Khalid Alsumair,; Fadhi Darwish Alrashidi,; Khaled Mohamed Aldhamadi,; Mtaib Madlool Algithi,; Obaid Munahi Almutakhaffi,; Faihan Saud Alnawmesi,; Ayed Alhumaidi Alazmi,; Norah Othman Alnahedh,; Faris Suwailem Alzabni,; Mutlak Obaid Al Azmi,; Nasser Abdullah Albaker,; Majed Fahad Alsalhani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The worlds health is still seriously threatened by infectious diseases which are made worse by globalization climate change and fast urbanization. Coordination of efforts across various sectors is necessary for the effective control and prevention of infectious diseases especially in public health settings. Nursing professionals and epidemiologists who are essential to patient care disease surveillance and data-driven decision-making are among the main contributors to these initiatives. Methods: This review explores the roles and collaboration between nursing professionals and epidemiologists in the control of infectious diseases. We examined current literature, reports, and case studies to identify the key responsibilities of each profession, their interactions in epidemic prevention, and the strategies employed to manage infectious disease outbreaks. Results: Nurses have a essential part in the front-line organization of infectious diseases done patient care, public outreach, and health education. As the first opinions of connection for patients, they help in tentative the range of disease by following to contamination regulator processes. Epidemiologists, make helps by investigating tendency analysis and disease investigation. Community health databases and involvement policies are knowledgeable by their results. Conclusion. For communicable diseases to be efficiently exact and vetoed, epidemiologists and nursing professionals must work together. Despite obstacles including inadequate funding, inadequate training, and communication difficulties, both professions can work together to prevent outbreaks and enhance disease control.